2002
DOI: 10.1007/s005950200078
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy for Perforated Gastric Malignant Lymphoma: Report of a Case

Abstract: We herein report the case of a 65-year old man with gastroduodenal malignant lymphoma (diffuse large B-cell type) accompanied with a bulbar perforation. A pancreaticoduodenectomy was performed because the duodenal second portion and pancreatic head were involved. However, extensive lymphadenectomy was not carried out because many lymph nodes were involved. The postoperative course was uneventful and CHOP therapy (pirarubicin 30 mg/m2, cyclophosphamide 500 mg/m2, vincristine 1 mg/m2, prednisolone 30 mg/m2) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Gastrointestinal perforation due to lymphoma may extend into sepsis and/or peritoneal dissemination of disease, resulting in a poor outcome and a mortality rate of about 60% [ 3 , 9 ]. A literature survey revealed reports of four cases of perforated duodenal lymphoma in Japan through 1980–2017 (written in Japanese without English abstracts [ 22 – 25 ]). The clinical characteristics of these four cases plus our own are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal perforation due to lymphoma may extend into sepsis and/or peritoneal dissemination of disease, resulting in a poor outcome and a mortality rate of about 60% [ 3 , 9 ]. A literature survey revealed reports of four cases of perforated duodenal lymphoma in Japan through 1980–2017 (written in Japanese without English abstracts [ 22 – 25 ]). The clinical characteristics of these four cases plus our own are summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative course was uneventful and chemotherapy was effective in eliminating the involved lymph nodes. Authors concluded, that the choice of surgical resection is very important in patients with perforated gastric lymphoma, since chemotherapy should be started as soon as possible after surgery [4].…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous perforation has been reported from 1% to 5% of cases of primary gastric lymphoma and commonly occurs after chemotherapy and irradiation [3]. Emergency surgery is usually performed but the prognosis in cases of perforated gastrointestinal lymphoma is very poor [4]. This report describes a case of a young man with spontaneous perforation of primary gastric malignant lymphoma and diffuse peritonitis without prior chemotherapy.…”
Section: Introductionmentioning
confidence: 92%